TOWARDS A LOCALIZED UNDERSTANDING OF VIOLENCE AGAINST CHILDREN AND ADOLESCENTS IN AFRICA - Kakuru, Doris M. (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2022)
Despite global and African continental efforts to curb violence against children (VAC), it is the fourth leading cause of death for young people aged 15 to 19 in Africa, according to a 2021 UNICEF report. In introducing this special issue on VAC in Africa, I contend that violence prevention and response efforts ought to be situated in local understandings of how violence is inflicted and experienced. Sociocultural and political ideals and values present in Africa nurture an atmosphere in which adults exercise power over children’s lives and can inflict harm upon them if they choose. Age-based power (adultism) facilitates VAC. Therefore, this special issue is underpinned by childism as a framework for challenging adultism in an effort to achieve a contextualized understanding of VAC in Africa, and how best to respond to and ultimately prevent it.